Prinsip dan Peran Logika sebagai Dasar Penalaran Ilmiah di Era Informasi - Andaryanto Andaryanto; Jeffri Wahyu Santoso; Agung Winarno (Universitas 45 Surabaya, 2024)
Logic has a very important role in the development of knowledge and studies of certain knowledge. As a science, it is the basis for determining straight, precise and healthy thinking. Because the function of logic is to investigate, formulate and apply the laws that are adhered to. Logic is a field of science that focuses on the principles of valid and consistent reasoning. Its role is very important in the process of systematic and rational thinking, especially in the era of rapidly developing information. In the context of information technology, logic functions as a basis for understanding and filtering various information received every day. This article aims to provide an introduction to the principles and role of logic as a basis for scientific reasoning in facing the challenges of the information era. The focus of this article is the relationship between logic, information analysis, and rational decision making. The purpose of this discussion is for readers to better understand the importance of using logic in sorting valid information, as well as improving critical thinking skills in dealing with various incoming data. This article also discusses the basic principles of logic, which are important in assessing and constructing rational arguments in the world of information.